"The Revolution Will Be Televised (With Apologies to Gil Scott-Heron)". Issue 2 (August 2021) - Alexander, Bryant Keith
I use the iconic spoken word poem, "The Revolution Will Not be Televised" by Gil Scott-Heron to chart a series of reflections on my childhood engagement of the piece for high speech tournaments. Then ground the reflection in current day commentary on the nature of revolution, protest, civil rights protest, the Black Lives Matter movements, issues of diversity, equity and inclusion (DEI), and the notion of antiracism.